Perceived Role of Dietary Fiber in Healthy Diet and its Intake Pattern among Educated Urban Population - Rahim, Abu Torab MA; Choudhury, Rumana (Bangladesh Journal of Nutrition, 2015)
Dietary fiber (DF) is now considered as a part of healthful diet because it plays an important role in preventing many of organic diseases. A survey was conducted to evaluate the perceived role of DF in healthy diet and its intake level among educated urbanites of Dhaka city. For dietary information, a 24 hours recall method along with a 7 day food frequency questionnaire was used. The findings show that the respondents were aware of DF and were able to name fiber rich foods. They perceived that fruits and vegetables are the rich source of DF. But fiber consumption frequencies showed that majority of them do not take fruits and vegetables everyday. As a result DF intake of the respondents was found 7.87 g/day, far below the recommended level (25-35 g/day or 10 g/1000 Kcal). Thus the study revealed that though the health benefits of DF was perceived and recognized by our educated population but they do not practice it.